METHOD OF PRODUCTION AND RESEARCH OF STRUCTURE OF SPINEL-PEROVSKITE COMPOSITE MATERIAL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses a composite material synthesized from cobalt carbonate and lanthanum oxide, chromium oxide and manganese. The phase composition, crystal parameters of the lattices and the type of crystal system were studied by X-ray method. According to the results of the X-ray phase study, it was found that the synthesized sample is a two-phase composite of cobalt chromite and lanthanum manganite in difgerent quantities. Lanthanum manganite in the composite material is formed in rhombic symmetry with the following parameters of crystal lattices: a=5.5213, b=5.4851, c=7.770Å, Z=4, and cobalt chromite is synthesized in cubic symmetry with the following parameters of crystal lattices: a=8.3306, b=8.3306, c=8.3306Å, Z=8.
Keywords: chromium complex, manganite, composite, sol-gel process, crystal structures, spinel, perovskite, multiferroic oxides